PENGARUH EFESIENSI, EFEKTIFITAS ASSETS TERHADAP LEVERAGE DAN DAMPAKNYA TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2009-2014 - Melani, Maria Magdalena (JURNAL AKUNIDA, 2017)
This research is aims to analyze the influence of efficiency, effektiveness of assets on leverage and its impact on stock returns on coal mining sector companies listed on the stock exchange Indonesia period 2009-2014. This research used purposive sampling method and obtain research samples as many as 9 companies doing an IPO on the Stock Exchange. Methods of analysis of research data using descriptive statistics for the description of the object of research, simultaneous test methods ( F test ) to assess the assumptions of multiple regression equations, and to test hypotheses using sub model of structure 1 test and sub model of structure 2 test. The test results showed simultaneous NPM, TATO, and DER has a significant effect on stock exchange. In Partial NPM significant positive effect on stock exchange, DER significant negative effect on stock exchange, and NPM significant negative effect on DER.Keywords : Stock Exchange, Debt of Equity Ratio, Net Profit Margin, and Total Asset Turn Over